Priority Setting in Norwegian Municipal and Health Care Services: A Thematic Analysis of Public Consultation Documents - Marius L. Torjusen; Eli Feiring; Mathias Barra; Nina Køpke Vøllestad; Carl Tollef Solberg (Tidsskrift for Omsorgsforskning)
Background: Despite Norwayʼs long history of open priority setting in healthcare, formal priority setting in municipal health and care services had been lacking prior to the publication of a Norwegian official report (English: Green paper, Norwegian: NOU) on the topic in 2018 (the Blankholm report). This article examines the reception of the reportʼs proposals from different stakeholders. Methods: We analysed 123 public consultation documents on the Blankholm report using a combined deductive and inductive thematic analysis. The consultation bodies represented the views of stakeholders, including patient and professional organisations, directorates, academic institutions, hospitals, and municipalities. Results: Our analysis resulted in two main themes: 1) Concerns about whether the proposed criteria are fit for purpose and 2) Concerns about infringing upon the principle of municipal autonomy and scepticism regarding whether the proposed priority setting process will enhance municipal services. Conclusion: Although there is acceptance for the necessity of priority setting, several issues remain. These issues relate to the proposalsʼ lack of definition, the complexity of municipal health and care services, and a distrust between municipalities and the central government.